Features of introduction of VoIP-telephony services - Bilash, D. A. (ХНУРЕ, 2021)
The analysis of the peculiarities of the creation of voice transmission technology through packet networks is performed in the work, taking into account that the role of the PBX is performed by the virtualized cloud platform. The work is a review work and is devoted to the promotion of the use of modern cloud technologies within the concept of Industry 5.0.
Keywords: VoIP; Telephony